PENINGKATAN PENGETAHUAN KADER POSYANDU MELALUI EDUKASI GIZI DAN PEMANFAATAN APLIKASI AKZI BUMIL - Yanuarti Petrika; Desi; Wiwik Sundari (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Chronic Energy Deficiency (CED) occurs due to prolonged insufficient intake of protein and energy, which often affects women both before and during pregnancy. One of the efforts to prevent CED in pregnant women is consuming adequate energy and protein according to their needs. Additionally, nutritional intake is influenced by the pregnant woman's knowledge about nutritional adequacy during pregnancy. The design of a pregnancy nutrition expert system model aims to assist pregnant women in determining healthy meal plans and monitoring their dietary patterns to achieve an ideal body weight. The objective of this community service program is to enhance the knowledge of Posyandu cadres about nutrition for pregnant women, enabling them to disseminate this information during Posyandu sessions. Additionally, it aims to equip the cadres with skills to use the AKZI Bumil application before introducing it to pregnant women. The methods for this community service program include providing education on maternal nutrition to cadres and introducing the AKZI Bumil application. Results: After the nutrition education, there was an increase in knowledge among 9 participants, with a statistically significant difference (p=0.046). Additionally, 66.7% of cadres found the application user-friendly and beneficial for managing maternal health data. Most cadres considered the content appropriate for their needs, although some reported errors and suggested adding variables for nutritional monitoring during pregnancy.